Pelatihan Family Caregiver Dalam Merawat Lansia Dengan Masalah Gangguan Kognitif - Dianis Wulan Sari; Pratiwindya Sudarsiwi, Neisya; Fitryasari, Rizki; Nashiruddin Habibie, Aziz; Fitrotul 'Aini, Nauvila; Arifah Astri, Nur; Farapti, Farapti; Misbahatul Mar’ah Has, Eka (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
Cognitive impairment and dementia place a significant burden on families in care. Those caring for older adults with dementia often face extraordinary emotional, physical, and financial challenges. Therefore, families and older adults need to maximize their role and provide support to reduce the burden they feel. Objective: This Community Service aims to increase the knowledge and skills of family caregivers in caring for older adults with cognitive impairment problems. Activities are carried out by providing counseling and demonstrations. The partner involved in the activity is the Kertosono Community Health Center. Activities are evaluated using pre-post tests. The average score of participants at the pretest was 5.36 and increased at the posttest to 8.46, so there was an increase in family caregivers' knowledge regarding cognitive impairment problems. The difference between the pre-test and post-test significance values ​​is 0.000, this value is <0.05 which explains that there is a significant difference between the pre-test and post-test scores. Training is useful for improving the knowledge and skills of family caregivers in caring for older adults with cognitive impairment problems.